Voided urine versus bladder washing cytology for detection of urothelial carcinoma: which is better?. (4th July 2017) - Keller, Anna Krarup; Jensen, Jørgen Bjerggaard
Abstract: Objective: Cytology is recommended as part of the follow-up of high-grade non-muscle-invasive bladder cancer (NMIBC). However, currently there are no solid guideline recommendations regarding the use of voided urine versus bladder washing for cytology as part of the diagnosis or follow-up of NMIBC. The aim of this study was to investigate whether the cytological outcome was equal regarding the two techniques. Materials and methods: The authors reviewed all outpatient flexible cystoscopies carried out in their department in 2013. Patient records in the registry of pathology were examined and those with simultaneous urine and bladder washing cytology were included. Previous urothelial disease and positive histology within 3 months after the cystoscopy were registered. Results: A total of 1458 patients had both voided urine and bladder washing cytology and were included in the study, of whom 643 (44%) had a history of urothelial disease. An equal outcome of urine and bladder washing cytology was found in 1447 patients (99.2%). For the remaining 11 patients, only four patients underwent further examinations based on cytology findings in addition to what had already been planned after cystoscopy. Of the included patients, 100 (6.9%) had a positive histological outcome within 3 months. Conclusions: In most patients, no relevant difference between voided urine and bladder washing cytology was observed. Therefore, if cytology is indicated, it is recommended to use the test that is most readily available locally. The additional gain in using both urine and bladder wash is minimal, and can therefore be discarded.